The Pak Wigah Grand Mosque - Hussain Ahmed; Kamil Khan Mumtaz (Journal of Traditional Building, Architecture and Urbanism, 2023)
The architecture of the Islamic world is unique in the way that it is able to express the doctrines of faith by virtue of material form. The “style” of this building tradition can be characterized by the use of geometric patterns and intricately detailed ornamental forms that create an overwhelming sense of serenity and spiritual beauty. This article examines the design process involved in the planning and construction of a traditional mosque through the example of the Pak Wigah Grand Mosque, designed by Kamil Khan Mumtaz and built by Dr. Hafiz Muhammad Farukh Hafeez.